2011
DOI: 10.1021/nn2001849
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermopower of Graphene Films with Oxygen Plasma Treatment

Abstract: In this work, we show that the maximum thermopower of few layers graphene (FLG) films could be greatly enhanced up to ∼700 μV/K after oxygen plasma treatment. The electrical conductivities of these plasma treated FLG films remain high, for example, ∼10(4) S/m, which results in power factors as high as ∼4.5 × 10(-3) W K(-2) m(-1). In comparison, the pristine FLG films show a maximum thermopower of ∼80 μV/K with an electrical conductivity of ∼5 × 10(4) S/m. The proposed mechanism is due to generation of local di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(149 citation statements)
references
References 56 publications
7
141
1
Order By: Relevance
“…108 With the introduction of defects in graphene, values of S and ZT can be increased further. 109 Xiao et al 110 reported maximum thermopower of 700 μV/K at 575 K with oxygen plasma treatment on few layer graphene. Though the electrical conductivity of the sample was determined to decrease from 5 × 10 4 S/m to 10 4 S/m, the increased thermopower resulted in a significant increase of power factor.…”
Section: Nitrogen Functionalizationmentioning
confidence: 99%
“…108 With the introduction of defects in graphene, values of S and ZT can be increased further. 109 Xiao et al 110 reported maximum thermopower of 700 μV/K at 575 K with oxygen plasma treatment on few layer graphene. Though the electrical conductivity of the sample was determined to decrease from 5 × 10 4 S/m to 10 4 S/m, the increased thermopower resulted in a significant increase of power factor.…”
Section: Nitrogen Functionalizationmentioning
confidence: 99%
“…Graphene (monolayer [38,39] and bilayer [40]) exfoliated on a SiO 2 =Si substrate, for example, provides a significant thermoelectric response and the usual temperature dependence of S can be overcome on a SiC substrate [41]. Performance improvements have been achieved through O plasma treatment [42] and molecular decoration [43]. Interestingly, high-density defects can also have positive effects [44].…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of thermoelectricity, the in-plane thermal conductance of graphene [31] is higher than pristine MoS 2 , which makes graphene useful for thermal management [32], but reduces its efficiency as a thermoelectric material. Since pristine monolayer MoS 2 has a lower thermal conductance, our aim below is to examine whether this material can form a basis for the design of high-efficiency thermoelectric materials.…”
Section: Introductionmentioning
confidence: 99%